Slides to Philosophy 167: Class 6 -- Galileo's Two New Sciences: Local Natural Motion -- Part 9. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 6, Part 9.